THE LEGAL STATUS OF PRISONERS IN ISLAMIC LAW AND THEIR LEGAL PROTECTION (PART 2) - Toshqulov Jo‘raboy (Scholar Express Journals, 2025)
This article explores the legal status of prisoners in Islamic law and their legal protection. It discusses the principles of war and peace in Islam, emphasizing justice, fairness, and the prohibition of indiscriminate violence. The study delves into key Islamic legal concepts such as jihad, war ethics, and the treatment of prisoners. It also examines treaties, military operations, the protection of civilians, and the role of the state in regulating war-related matters. References from the Qur’an, hadiths, and classical Islamic juristic texts provide a comprehensive view of how Islamic law governs wartime conduct and the rights of prisoners.
Keywords: Islamic law; prisoners; war ethics